Healthcare resource utilization and costs among patients with alpha-1 antitrypsin deficiency with liver and/or lung disease: a longitudinal retrospective study in the USA - May Hagiwara; Victoria Divino; Swapna Munnangi; Mark Delegge; Suna Park; Ed G Marins; Kaili Ren; Charlie Strange (Becaris Publishing Limited, 2024)
Aim: To evaluate all-cause and liver-associated healthcare resource utilization (HCRU) and costs among patients with alpha-1 antitrypsin deficiency (AATD) with liver disease (LD) and/or lung disease (LgD). Materials & methods: This was a retrospective analysis of linked administrative claims data from the IQVIA PharMetrics R Plus and the IQVIA Ambulatory Electronic Medical Records (AEMR) databases from 1 July 2021 to 31 January 2022. Patients with AATD in the IQVIA PharMetrics Plus database were included with≥1 inpatient or≥2 outpatientmedical claims≥90 days apartwith a diagnosis of AATD, orwith records indicating a protease inhibitor (Pi)*ZZ/Pi*MZ genotype in the IQVIA AEMR databasewith linkage to IQVIA PharMetrics Plus. For a patient's identified continuous enrollment period, patient time was assigned to health states based on the initial encounter with an LD/LgD diagnosis. A unique index date was defined for each health state, and HCRU and costs were calculated per person-year (PPY). Results: Overall, 5136 adult and pediatric patients from the IQVIA PharMetrics Plus and IQVIA AEMR databases were analyzed. All-cause and liver-associated HCRU and costs were substantially higher following onset of LD/LgD. Allcause cost PPY ranged from US $11,877 in the absence of either LD/LgD to US $74,015 in the presence of both LD and LgD. Among liver transplant recipients in the AATD with LD health state, liver-associated total costs PPY were US $87,329 1-year pre-transplantation and US $461,752 1-year post-transplantation. In the AATD with LgD and AATD with LD and LgD health states, patients who received augmentation therapy were associated with higher all-cause total costs PPY and lower liver-associated total costs PPY than their counterparts who did not receive augmentation therapy. Conclusion: Patients with AATD had increased HCRU and healthcare costs in the presence of LD and/or LgD. HCRU and healthcare costs were highest in the AATD with LD and LgD health state.